The Value of Kitsch. Hermann Broch and Robert Musil on Art and Morality - Patrizia C. McBride (Studies in 20th & 21st Century Literature, 2005)
This article examines the discourse on kitsch articulated by Austrian novelists Hermann Broch (1886-1951) and Robert Musil (1880-1942) between 1930 and 1950. In particular, I focus on the ways in which the two novelists draw the distinction of value between real and pseudo art (or kitsch). As I argue, their disagreement on this matter is emblematic of dilemmas that continue to confront aesthetic evaluation today. While Broch anchors value in a metaphysical realm on the outside of aesthetic discourse, assuming a late-idealistic notion of art, Musil frames the distinction between 'good' and 'bad' art within an empirical, relativistic, and immanent understanding of aesthetic experience. In the final section I draw on Hal Foster's notion of a "critical distance" (The Return of the Real, 1996) to discuss the advantages and limitations of the evaluative paradigms suggested by the two novelists.
Keywords: kitsch; Austria; Austrian literature; Hermann Broch; Robert Musil; real art; pseudo art; art; late-idealistic art; relativistic; aesthetic experience; Hal Foster; critical distance; The Return of the Real